A proposed future vision for the roles of the teacher in promoting technological innovation and the digital economy to achieve the Kingdom’s Vision 2030 - Alshami, Ghadah Shaker; Alghamdi, DaifAllah Ahmed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to present a proposed future vision for the teacher’s roles in supporting modern technological innovation activities that fulfill the requirements of the digital economy in the light of the Kingdom’s 2030 vision, by identifying the technological innovation activities that the teacher should know in the digital age and revealing the requirements of the digital economy that should be achieved in the light of the vision Kingdom 2030 AD; To achieve this goal, the researchers prepared a descriptive and analytical study that includes the requirements of the digital economy based on modern technological innovation activities in the light of the Kingdom’s 2030 vision. The questionnaire was used as a study tool, in which the sample consisted of (233) talented teachers and supervisors. The researchers reached a number of recommendations, most notably: Improving the recruitment of talented people. Teachers, preparing them, rehabilitating and developing them, the teacher is the main pillar of the educational process, and looking at the roles of the teacher is a necessity as it is the main entrance to confronting the education crisis in the contemporary reality, and adopting technology and innovation as basic drivers of economic growth in education in the digital age, where the strength of any economy is built on the extent of its technological progress Creating the infrastructure and investing in modern technologies in various aspects of contemporary life; This requires upgrading the future vision, and reconsidering the methods of traditional operations at all levels, as information and communication technology has become a way of life and not just a luxury tool limited to a specific field or a social elite.